2x-6x-65=63

Simple and best practice solution for 2x-6x-65=63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-6x-65=63 equation:


Simplifying
2x + -6x + -65 = 63

Reorder the terms:
-65 + 2x + -6x = 63

Combine like terms: 2x + -6x = -4x
-65 + -4x = 63

Solving
-65 + -4x = 63

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '65' to each side of the equation.
-65 + 65 + -4x = 63 + 65

Combine like terms: -65 + 65 = 0
0 + -4x = 63 + 65
-4x = 63 + 65

Combine like terms: 63 + 65 = 128
-4x = 128

Divide each side by '-4'.
x = -32

Simplifying
x = -32

See similar equations:

| 3(2x+9)=5(x-2) | | 2AH=V^2-U^2 | | 6x-50=10x+73 | | -0.7x+0.8x+8=-2 | | 2ln(x)=ln(x+6) | | 3x=(4x-15) | | 2y+8y-3=x | | 5p-4=2p+12 | | 6.9x-6+x-1.6= | | 31=5t+6 | | 180+17n=350 | | 8-24=3y-2 | | 0.7+0.8+8=-2 | | V^2=U^2+2AH | | s=5r^3t | | 1/3x+6=-4 | | 3m-3=24 | | S=7+4s | | 7b+5-7b-2=8 | | 1/2x-1=-5 | | 3c+(c+12)=124 | | 4.5/5 | | 20=S+13-4s | | 3c+(c+12)=24 | | 0.25x+7.5-0.75x=3 | | y=za | | -5(6(a)+2)=-15 | | 1/9+4=5 | | 2x=11+6 | | 3/8z-1=5 | | 0.24/48 | | 7x-3-6x=5+5x-13 |

Equations solver categories